Queixas subjetivas de memória e desempenho cognitivo em adultos acima de 50 anos - Bezerra, Izabela Alves de Oliveira (2016)
Studies show that subjective memory complaints (SMC) are very common in older adults and may be indicators of cognitive impairment associated with psychological factors (e.g., anxiety and depression) and cognitive impairment. The aim of this master thesis was to analyze the relationship between the prospective and retrospective memory complaints and performance on different measures of memory in people without dementia aged over 50 years. 81 volunteers of both sexes (68 women) with a mean age of 63 years (SD = 6.7) took part in the study. The procedure used in this study consists of two successive stages of evaluation. The first part includes screening tests of cognitive status and selection of participants, and questionnaires for assessing the prevalence of SMC. After this phase, we assessed semantic, episodic, working and prospective memory, the latter being tested through naturalistic tasks. Furthermore, a neuropsychological evaluation of various cognitive domains was performed, including attention, visual perception, language, processing speed, cognitive flexibility and inhibitory control. The prevalence of complaints in the sample was 53%. The results indicate that people with SMC have significantly higher prevalence of anxiety and depressive symptoms, lower overall score in prospective memory tasks and slowness in the execution of inhibitory control task. No significant differences were identified between the groups for performance in episodic, semantics and working memory tests. In the hierarchical regression analysis (stepwise method) we identified the symptoms of anxiety and performance in the long-term prospective memory task (based on time) as predictors of general and retrospectives memory complaints, but only anxiety as predictor of prospective complaints. We conclude, therefore, that different types of complaints are predicted by different variables. Retrospective complaints are related more significantly with symptoms of anxiety and objective performance. In the case of prospective complaints, they seem to reflect a distorted self-evaluation due to the symptoms of anxiety but without relationship with cognitive impairment. This work emphasizes the importance of including prospective memory tests in neuropsychological assessment protocols, as they showed greater sensitivity to detect deficits in healthy people.